La relevancia del otro en sociedades con temor al otro - Wingartz, Oscar (Bollettino Filosofico, 2019)
This paper is divided into two parts. The first one deals with historical, political, social and economic analysis of migrations since the Spanish conquest to our days passing through XIX century and North American presence and pressure on Caribbean trade. The second one focuses on philosophical issue of “otherness” and shows the impact of migrations on receiving societies. It underlines the logic of exclusion which regulates the relationship between USA and Mexico, and some of the problems involved, such as drug trafficking and social violence. The essay ends with a reference to José Martí and his negation of the ontological and epistemological status of the issue “struggle of races”. Keywords: Conquest, Domain, Violence, Otherness, Latin America